Ergo-assessment of Locomotive Drivers’ Traffic Environment - Sumpor, Davor; Jurum-Kipke, Jasna; Petrović, Dalibor (Promet - Traffic&Transportation, 2012)
While operating a locomotive or a railcar the engine drivers are exposed to the action of several simultaneous factors of disturbances from the traffic environment, and therefore their reliability and safety are reduced. The human-determined physical, sensor and cognitive factors are not only the attributes of the engine driver, but also include influences from the traffic environment, due to the interaction in the “engine driver – traffic means – traffic environment” system. Traffic environment is defined in such a way that, among other things, it includes also the working environment of the drivers cab and the recent traffic situation. The action of factors of temporary subjective disturbances and/or permanent psychological and physiological changes, depend not only on the individual endurance of engine drivers, but also significantly on the type of locomotive or railcar operated by the engine driver, as well as on the fact whether the traffic is intended for the transport of passengers and/or freight, or a shunting engine is involved. The ergo-assessment based on a survey of 50 respondents yielded the final results that are almost identical to the results of ergo-assessment obtained during the formation of the methodology of cognitive ergo-assessment on a sample of 31 respondents. In both cases the surveyed respondents were engine drivers who in practice operate all types of locomotives and railcars, who have acquired engine driver secondary school qualifications and have passed vocational testing for all types of locomotives and railcars. Systemic ergo-assessment of the intensity of the overall psychophysical effort is possible by introducing the index of importance which is used in case of all engine drivers to integrally and equally recognise also the influence of the percentage of occurrence of a certain factor of subjective disturbance and influence of the average assessment of the subjective disturbance intensity, thus allowing an insight into the structure of a system of simultaneous ergo-assessment factors and isolation of ten dominant ergo-assessment factors. Partial cognitive ergo-assessment and inter-comparison of the intensity of subjective disturbances have indicated the types of locomotives and/or railcar compositions in which the maximum partial intensity of disturbance is due to the following factors regarding the working ambient of the drivers cab: visibility, intensity of the difficulty of operation, and intensity of disturbance of the audible traffic noise.KEY WORDS: traffic environment, cognitive ergo-assessment, dominant factors of subjective disturbances, assessment parameters, safety and reliability